دراسة أداء وفعالية ترميز الشبكة الخطي العشوائي في تحقيق النقل الموثوق للبيانات في الشبكات اللاسلكية ذات الضياع - محمد حجازية; أحمد إبراهيم (Tishreen University, 2018)
تعاني الشبكات اللاسلكية من الضياع المتكرر للرزم لأسباب عديدة منها التداخلات والتصادم والخفوت، مما يجعل من الوسط اللاسلكي وسط غير موثوق لنقل البيانات. أبرز طرق ضمان وثوقية النقل عبر هذا الوسط هي باستخدام بروتوكول التحكم بالنقل (TCP) وبروتوكول إعادة الطلب التلقائي (ARQ). مؤخراً وجد ترميز الشبكة كتقنية جديدة تغير من طريقة التوجيه التقليدية (خزن-وَ-وجه) في الشبكات إلى طريقة أكثر ذكاءً وفعالية هي (رمز -وَ-وجه)، مما يسهم في زيادة سعة وإنتاجية النقل لهذه الشبكات. تم في هذا البحث استخدام ترميز الشبكة الخطي العشوائي كتقنية واعدة تهدف إلى تحقيق النقل الموثوق للبيانات في الشبكات اللاسلكية ذات الضياع، وكذلك دراسة التحسين الذي تقدمه لأداء هذه الشبكات بحالتي الإرسال الوحيد والمتعدد. لتقييم فعالية هذه التقنية ومقارنة أدائها مع أداء بروتوكولات النقل الموثوق تم استخدام محاكي الشبكات NS3. وقد بينت نتائج المحاكاة تحقيق ترميز الشبكة الخطي العشوائي عملية النقل الموثوق للبيانات بإنتاجية أكبر وتأخير زمني وعدد عمليات إرسال أقل مقارنة بالبروتوكولين (TCP، ARQ). Wireless networks suffer from frequent loss of packets for many reasons such as interference, collision and fading. This makes wireless medium unreliable medium for data transfer. The main methods for ensuring the reliability in this medium are using transmission control protocol (TCP) and the automatic repeat request (ARQ). Recently, network coding has been found as new technology that changes the traditional forwarding method (Store- and- Forward)  in the networks to more effective and intelligent method (Code- and- Forward), which contributes to the increase of both capacity and throughput of these networks.   In this research, random linear network coding is used as promising technology that aims to achieve the reliable transfer of data in losing wireless networks, and studying the enhancement that this technology presents to the performance of these networks in unicast and multicast transmission. For evaluating the efficiency of this technology and comparing its performance with the performance of reliable transfer protocols, we use the networks simulator (NS3). Simulation results showed that random linear network coding achieve the reliable transfer of data with bigger throughput and less delay and number of transmission compared with the protocols (TCP, ARQ).